2011
DOI: 10.1093/ndt/gfr472
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of sulfobutylether- -cyclodextrin (SBECD) in subjects on hemodialysis

Abstract: Hemodialysis can significantly reduce levels of SBECD in subjects with end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…These observations are consistent with previous reports on dialysis of SBECD. From a model of SBECD pharmacokinetics in ESRD subjects receiving IV voriconazole every 12 hours, it was predicted that hemodialysis (2‐ to 6‐hour sessions) would remove on average 46% of the total systemic load of SBECD . No adverse events in this study were attributed to SBECD.…”
Section: Discussionmentioning
confidence: 79%
“…These observations are consistent with previous reports on dialysis of SBECD. From a model of SBECD pharmacokinetics in ESRD subjects receiving IV voriconazole every 12 hours, it was predicted that hemodialysis (2‐ to 6‐hour sessions) would remove on average 46% of the total systemic load of SBECD . No adverse events in this study were attributed to SBECD.…”
Section: Discussionmentioning
confidence: 79%
“…However, most previous studies used parent cyclodextrins, notably α‐cyclodextrin, β‐cyclodextrin or methylated β‐cyclodextrin. It has been shown that SBECD, a rationally designed β‐cyclodextrin derivative, has a more favourable toxicological profile compared to the parent cyclodextrins . Although intravenous SBECD causes vacuolation of renal tubules in a dose‐dependent manner in animal models, SBECD‐induced vacuolation of renal tubules is not associated with alteration of renal function and is reversible following cessation of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SBECD, a rationally designed b-cyclodextrin derivative, has a more favourable toxicological profile compared to the parent cyclodextrins. 9,33,34 Although intravenous SBECD causes vacuolation of renal tubules in a dosedependent manner in animal models, SBECD-induced vacuolation of renal tubules is not associated with alteration of renal function and is reversible following cessation of treatment. 9,35 In fact, there are several studies that demonstrate no correlation between the SBECD exposure and deterioration of renal function in patients with compromised renal function.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although SBECD has been shown to be eliminated in dialysate, it does accumulate to a greater extent than delafloxacin. [10][11][12] Product labeling for delafloxacin recommends an IV dose reduction for patients with severe renal impairment from 300 mg every 12 hours (Q12h) to 200 mg Q12h due to the presence of SBECD in the formulation, with no change in the recommended oral dose of 450 mg Q12h. 1 Delafloxacin in its present IV formulation containing SBECD does not have dosing recommendations for patients with ESRD.…”
mentioning
confidence: 99%